2016
DOI: 10.1159/000452889
|View full text |Cite
|
Sign up to set email alerts
|

Are Basophils and Mast Cells Masters in HIV Infection?

Abstract: The World Health Organization AIDS epidemic update estimates that more than 37 million people are living with HIV infection. Despite the unprecedented success of antiretroviral treatments, significant challenges remain in the fight against HIV. In particular, how uninfected cells capture HIV and transmit virions to target cells remains an unanswered question. Tissue mast cells and peripheral blood basophils can be exposed to virions or HIV products during infection. Several HIV proteins (i.e., envelope glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 81 publications
0
22
0
1
Order By: Relevance
“…Although they are the least abundant leucocytes [ 88 ], our study has found basophils to explain the greatest variation in the CD4 + count following the lymphocytes. However, the direct contact between human basophils and CD4 + T cells is known to mediate viral trans-infection of T cells through the formation of viral synapses [ 89 , 90 ]. Also, the presence of basophils and other white blood cells in the blood is affected by underlying infection [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although they are the least abundant leucocytes [ 88 ], our study has found basophils to explain the greatest variation in the CD4 + count following the lymphocytes. However, the direct contact between human basophils and CD4 + T cells is known to mediate viral trans-infection of T cells through the formation of viral synapses [ 89 , 90 ]. Also, the presence of basophils and other white blood cells in the blood is affected by underlying infection [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basophils have long been marginalized in immunological studies and they were erroneously regarded as minor relatives of mast cells. Recent advances in analytical tools for basophils have highlighted the non‐redundant roles of basophils not only in allergic inflammation but also in autoimmune disorders, microbial infections, immunodeficiencies, and cancer . In murine models, there is convincing evidence of the heterogeneity of basophils expressing the TSLP receptor or the IL‐3 receptor .…”
Section: Closing Thoughtsmentioning
confidence: 99%
“…Human mast cells and basophils were first described and named in 1878 and 1879, respectively, by Paul Ehrlich who discovered their property to be stained by specific dyes . Mast cells and basophils are important cells of the immune system with critical role in allergic and autoimmune disorders, microbial infections, cardiovascular diseases, immunodeficiencies, and cancer …”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial proteins can induce the release of mediators (e.g., histamine, PGD 2 , TNF-α, and cysteinyl leukotrienes) from human mast cells [22, 117-119]. Initial studies with KIT mutant mice showed that mast cells are crucial for protection against enterobacterial infection in the cecal ligation and puncture (CLP) model of sepsis [120, 121].…”
Section: Mast Cells In the Host Defense Against Pathogensmentioning
confidence: 99%